Intranasal immunization with C5a peptidase prevents nasopharyngeal colonization of mice by the group A Streptococcus. - Ji, Y (1997)
Early inflammatory events are initiated by phased production of C5a and interleukin-8 in tissue. Most serotypes of group A streptococci express a surface-bound peptidase (SCPA) which specifically cleaves mouse and human C5a chemotaxins. This study investigates the impact of SCPA on colonization of the nasopharyngeal mucosa of mice and evaluates its potential to induce protective immunity. Two strains, serotypes M6 and M49, which contain insertion and deletion mutations in the SCPA gene (scpA) and represent the two major subdivisions of group A streptococci, were characterized and compared in a mouse intranasal infection model. In this model, SCPA mutants were more rapidly cleared from the nasopharynges of inoculated mice compared with wild-type strains. A 2,908-bp fragment of scpA49 gene, obtained by PCR, was ligated to the expression vector pGEX-4T-1 and expressed in Escherichia coli. The affinity-purified deltaSCPA49 protein proved to be highly immunogenic in mice and rabbits. Although the purified deltaSCPA49 immunogen lacked enzymatic activity, it induced high titers of rabbit antibodies which were able to neutralize peptidase activity associated with M1, M6, M12, and M49 streptococci in vitro. This result confirmed that antipeptidase antibodies lack serotype specificity. Intranasal immunization of mice with the deleted form of the SCPA49 protein stimulated significant levels of specific salivary secretory immunoglobulin A (IgA) and serum IgG antibodies and reduced the potential of wild-type M1, M2, M6, M11, and M49 streptococci to colonize. These experiments suggest a new approach to vaccine development for prevention of streptococcal pharyngitis.